Palladium and Platinum 2,4-cis-amino Azetidine and Related Complexes - Yoshizawa, Akina; Feula, Antonio; Leach, Andrew G.; Male, Louise; Fossey, John S. (Frontiers in Chemistry, 2018)
Seven N,N’-palladium(II) chloride complexes, one N,N’-palladium(II) acetate complex of 2,4-cis-azetidines where prepared and analysed by single crystal XRD. Two platinum(II) chloride N,N’-complexes of 2,4-cis-azetidines where prepared and analysed by single crystal XRD. Computational analysis and determination of the %Vbur was examined conducted. A CNN’ metallocyclic complex was prepared by oxidative addition of palladium(0) to an ortho bromo 2,4-cis-disubstituted azetidine and its crystal structure displays a slightly pyramidalised metal-ligand orientation.